Complete genome sequence of Pseudomonas brassicacearum strain L13-6-12, a biological control agent from the rhizosphere of potato - Zachow, Christin (Stand Genomic Sci, 2017)
Pseudomonas brassicacearum strain L13-6-12 is a rhizosphere colonizer of potato, lettuce and sugar beet. Previous studies have shown that this motile, Gram-negative, non-sporulating bacterium is an effective biocontrol agent against different phytopathogens. Here, we announce and describe the complete genome sequence of P. brassicacearum L13-6-12 consisting of a single 6.7 Mb circular chromosome that consists of 5773 protein coding genes and 85 RNA-only encoding genes. Genome analysis revealed genes encoding specialized functions for pathogen suppression, thriving in the rhizosphere and interacting with eukaryotic organisms.